STUDENTS’ SCIENTIFIC COMMUNICATION SKILLS IN STEM ROBOTICS LEARNING THROUGH TRANSCRIPT-BASED LESSON ANALYSIS (TBLA) - Azizah Putri Islami; Nova Susanti; Rahma Dani (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
This study aims to analyze the scientific communication skills of junior high school students who participate in robotics extracurricular activities through STEM-based learning with the Transcript-Based Lesson Analysis (TBLA) approach. The research was conducted at Nurul Ilmi 1 Integrated Islamic Junior High School, Jambi City, involving four groups of robotics extracurricular students. Each group is involved in the robot creation and testing project, and the interactions between group members during the activity are recorded, transcribed and analyzed using TBLA instruments. The analysis was carried out in a descriptive quantitative manner by calculating the frequency of the occurrence of six indicators of scientific communication, which were then converted into percentages. This process is done with the help of an excel application. Preliminary results show that the most dominant indicators are the ability to convey work verbally and the use of simple scientific terms, while the indicator asking about how robots work appears the least. These results provide an overview of students' scientific communication tendencies in the context of robotics activities, as well as provide a basis for the development of STEM learning models that can improve students' scientific communication skills through non-formal approaches